Research and development the measurer of the low frequency vibrations for the control system of normalized parameters of production factors - Костенко, Виталий Леонидович; Ядрова, Марина Васильевна; Николенко, Анатолий Александрович; Поперека, Екатерина Дмитриевна (Technology audit and production reserves, 2015)
It is developed and researched the measurer low-frequency vibrations (frequencies less than 1 Hz) based on bimorph with optoelectronic control for the control system of normalized parameters of the production factors. Development and research are conducted to add the automated information-measuring system by the channel of parameter control of the low-frequency vibrations (up to 1 Hz), for automation of measurement and control process, improve accuracy and performance monitoring of normalized parameters, as well as to provide automatic compensation of the nonlinearity of the piezoelectric bimorph piezoelectric element in the process of monitoring and calibration. The computer simulation of the matching device and bimorph piezoelectric element is conducted to investigate the processes, optimization of parameters and evaluation of frequency characteristics of the device. This study has allowed determining the timing of the control algorithm implemented by a microcontroller, the frequency change of control action and a maximum frequency of external influence on the piezoelectric transducer, i.e. the maximum frequency of measured vibrations. To automate the process of measuring and improving the accuracy and productivity of normalized control parameters it is necessary use a microcontroller with integrated module of width-pulse modulation included in the circuit of the position adjusting of bimorph piezoelectric element. BPE matching with a microcontroller can be achieved with a pulsed matching device. The results of studies are useful for the development of devices to expand the functionality of the control system of production factors and can be used in sanitary - hygiene inspection of workplaces.